2016
DOI: 10.5433/1679-0359.2016v37n4p2123
|View full text |Cite
|
Sign up to set email alerts
|

Tissue composition and allometric growth of tissues from commercial cuts and carcass of Texel lambs slaughtered with different weights

Abstract: In this study, we evaluated the tissue composition, the ratios between different issues, and the allometric growth of tissues from the commercial cuts neck, shoulder, rib, and leg, and of the carcass of Texel lambs. Thirty uncastrated male lambs born from single calvings were used in this experiment. Lambs were weaned, confined individually, and distributed into five treatments with six replications. Each treatment consisted of a predefined slaughter weight (T23 -initial slaughter, T25, T30, T35, and T40). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
7
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 10 publications
3
7
0
4
Order By: Relevance
“…For instance, older animals may display larger accumulation of fat, which is often not appreciated by consumers. Carvalho et al (2016) stated that bone and muscle tissues have an early growth, whereas fat has a late growth in the different commercial cuts and carcass. In this regard, there is a trend for a decrease in muscle:fat ratio as animals age, which requires more in-depth knowledge of the potential of the lamb and hogget categories concerning carcass characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, older animals may display larger accumulation of fat, which is often not appreciated by consumers. Carvalho et al (2016) stated that bone and muscle tissues have an early growth, whereas fat has a late growth in the different commercial cuts and carcass. In this regard, there is a trend for a decrease in muscle:fat ratio as animals age, which requires more in-depth knowledge of the potential of the lamb and hogget categories concerning carcass characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…animais abatidos com pesos elevados. Assim, o excesso de gordura é um fator limitante na produção de carcaças de cordeiros abatidos com peso elevado, exigindo a identificação de raças e cruzamentos capazes de gerar carcaças mais desejáveis, especialmente, quando os animais são alimentados de modo a atingir pesos elevados (CARVALHO et al, 2016).…”
Section: Resultsunclassified
“…No entanto, o costilhar pode sofrer novas divisões e, obter-se as costelas fixas (short rack ou carré curto), costelas flutuantes (french rack ou carré francês), baixo (peito) e o lombo com vazio (lombo com fraldinha). Essa nova fragmentação do costilhar, permite melhor aproveitamento culinário, homogeneidade na qualidade e maior valorização comercial desses cortes comerciais, por essa razão a necessidade de seu estudo.A partir dos resultados apresentados, pode-se ressaltar que os cortes comerciais dos animais abatidos mais leves apresentaram maiores rendimentos de músculo e menores de gordura, consequentemente, uma maior porção comestível obtida pela relação tecidual músculo/gordura, corroborando comAlves et al (2015) eCarvalho et al (2016).…”
unclassified
See 1 more Smart Citation
“…This result agrees with Menezes et al (2013) who demonstrated that carcass yield increased with body weight. However, the development of organs showed different growth stages, as each animal reached maturity at different physiological ages (Carvalho et al, 2016).…”
Section: Fatty Acid Profile Levels Of Replacementmentioning
confidence: 99%